Sustainability Signaling and Firm Value: Carbon Emission Disclosure and Environmental Performance Ratings in Shaping Firm Value in Indonesia - Linda Dwi Puspita Sari; Syahriar Abdullah; Supartini Supartini; Susilaningtyas Budiana Kurniawati (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to analyze the effect of carbon emission disclosure and the environmental performance ratings of the corporate environmental performance rating program on firm value, both partially and simultaneously, in companies listed on the Indonesia Stock Exchange for the period 2022–2024. Methodology: This study employs a quantitative causal-comparative approach using secondary data from corporate and regulatory disclosures. Carbon emission disclosure is treated as a form of corporate social accountability, reflecting firms’ responses to environmental expectations. Firm value is measured using Tobin’s Q, while environmental performance is represented by the environmental performance ratings, which function as a public policy instrument implemented by the Indonesian government. Statistical analysis is used to examine how public regulation shapes market responses to corporate environmental accountability. Main Findings: The results indicate that carbon emission disclosure does not have a significant effect on firm value. The environmental performance have a negative and significant effect on firm value. Simultaneously, carbon emission disclosure and the environmental performance ratings do not have a significant effect on firm value, indicating that environmental information is not yet a major consideration for investors. Novelty/Originality of this study: This study offers novelty by re-examining the effect of carbon emission disclosure and the environmental performance ratings on firm value using the most recent data from the 2022–2024 period. It assesses whether environmental aspects have been utilized by investors as signals in firm valuation and provides empirical contributions to environmental accounting literature and the formulation of sustainable business policies.